Assessment of health behaviors of primary school teachers based on their nutritional knowledge and physical activity: A cross-sectional study in the Asir Region - Amani Alhazmi; Maha Ali; Adam Dawria; Bayapa Reddy Narapureddy; Manal Mohammed Hawash (PLoS ONE, 2025)
Background Primary school teachers play a critical role as educators in imparting healthy eating behaviour and the importance of physical activity to prevent health issues. However, the teachers’ health behaviors have not been studied much, particularly in Saudi Arabia. Understanding these factors is essential to developing interventions that enhance teachers’ well-being and their ability to influence students positively. This study aims to assess nutritional knowledge and physical activity; to determine correlations between health behaviour factors and Body Mass Index (BMI), and evaluate BMI status concerning demographic factors among primary school teachers in the Asir Region, KSA. Methods A cross-sectional design was employed, involving 370 primary school teachers. Data were collected using a self-administered questionnaire that covered sociodemographic details, anthropometric measurements, physical activity levels, and nutritional knowledge. Statistical analyses included Pearson’s correlation and Chi-square tests, with significance at p < 0.05. Results Among the participants, 38.6% were overweight, and 33.5% were obese, with 76% of married teachers classified as overweight or obese. Only 9.0% exhibited excellent nutritional knowledge, while 25.0% demonstrated poor knowledge. The majority (84.0%) engaged in low or minimal physical activity. A weak but significant correlation was observed between nutritional knowledge and BMI (p < 0.05), whereas no significant associations were found between physical activity levels and either BMI or nutritional knowledge. Conclusion The study highlights critical gaps in nutritional knowledge and physical activity among teachers, emphasizing the need for targeted school-based health education programs. Improving teacher health behaviors could enhance their well-being and enable them to act as positive role models for their students.